Pelagic Bacteria and Viruses in a High Arctic Region: Environmental Control in the Autumn Period - Vladimir G. Dvoretsky; Marina P. Venger; Anastasya V. Vashchenko; Tatyana M. Maksimovskaya; Tatyana G. Ishkulova; Veronika V. Vodopianova (Biology, 2022)
In the marine environment, bacteria and viruses play a significant role in carbon fluxes, remineralization processes, and the infection of various organisms. We performed a survey in the northeastern Barents Sea, a region adjacent to the Arctic Ocean, to investigate spatial patterns of microbial plankton, after the main productive period, in October 2020. Two main water masses occurred in the study region—colder Arctic Water and warmer Barents Sea Water, representing transformed Atlantic Water. Multivariate analyses detected patchiness in the horizontal distribution of bacteria and viruses, and their abundances showed no clear association with the water masses. There was an obvious vertical pattern in microbial concentration, with the highest estimates in the upper layers. Surface viral and bacterial abundance varied in a wide range (2.20 × 105–10.7 × 105 cells·mL−1 and 0.86 × 106–14.98 × 106 particles·mL−1, respectively) and were correlated with each other. Bacterioplankton was dominated by small-sized cells (<2 μm, 0.04–0.06 µm3), and the average volume of bacterial cells tended to increase toward the seafloor. The ratio of viral to bacterial abundance (VBR) was 11 ± 1 and did not differ between water masses and depth layers. VBR were higher, compared to summer values, suggesting a strong impact of viruses on bacterioplankton, after the main productive season. Redundancy and correlation analyses showed that inorganic nutrients (nitrate and phosphate) and organic carbon from zooplankton were most responsible for the total variability in the microbial parameters. Water temperature and salinity, also, had a measurable impact, but their influence was lower. Bacterial abundance was lower than in other seasons and regions of the Barents Sea, while viral abundance was comparable, suggesting a stronger viral impact on Arctic marine bacteria in the autumn season.